Ashta Hydropower—Turning a Doubtful Concept into a Technological Trailblazer - Sobek, Martin (World Bank, Washington, DC, 2012)
International Finance Corporation (IFC) played a key role in helping the Republic of Albania structure and implements it first large public-private partnership (PPP) transaction in the energy sector, which brought a strong and reliable international investor into the country. Verbund, Austria's largest electricity company won a 35-year concession to build and operate the Ashta plant, the first major hydropower plant built in Albania in 30 years. Verbund will invest more than $220 million in the project, resulting in an expected savings on Albania's electricity imports in excess of $45 million during the first five years of the plant's operation. The Ashta hydropower plant is a great example of how IFC involvement can bring about real change by fostering innovative solutions.